PRAGMATIC PECULIARITIES OF ENGLISH SLANG IN ONLINE COMMUNICATION (Western European Journal of Linguistics and Education, 2024)
This article explores the use of slang in online environment from a pragmatic perspective. It analyzes the contexts and functions of slang expressions in online communication focusing on their social, linguistic and pragmatic peculiarities. This analysis provides a better understanding of the role of slang in the Internet communication, the social media space and its impact on the formation and maintenance of online communities. In the article will be discussed the roles and functions of English slang such as establishing social bonds, creating group identity, expressing emotional connotation. Modern slang in English, being integral part of language, represents one of the most urgent and contradictory problems of the modern lexicology. The paper provides examples of English slang terms mostly used by youth in online communication, particularly in social medias